ANALISIS PERBEDAAN MINAT MASYARAKAT KOTA MEDAN MENABUNG DI BANK SYARIAH DAN BANK KONVENSIONAL - Dewi Andriany (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This research nis aims for considering society interest for save money at Sharia Banks,considering societyinterest for save money at Conventional Banks. The sample was of this study was divided into Sharia Bank's customer and Conventionsl Bank's customer.